Exploring factors affecting astro-tourism development in Tanzania - Batinoluho, Ladislaus (School of Tourism, Universitas Ciputra Surabaya, 2024)
Factors affecting astro-tourism development in Tanzania have not been well established. The country has several national parks, and conservation areas, and its proximity to the equatorial location, make Tanzania a competitive destination for astro-tourism in Africa. Astro-tourism has the potential to impact on the local developing economies such as Tanzania. However, the factors that make Tanzania continue to lag in positioning itself as an astro-tourism destination are unknown. This study was conducted in Tanzania using qualitative and quantitative methods, involving 196 respondents who were purposively sampled and later on, randomly drawn from a population of over 1912 tourism stakeholders. The few available astro-tourism professionals operate in silos and are not coordinated. Tanzania lacks tourist observatories, and none of the major tourism players, including Hotel Association of Tanzania, Tanzania Association of Tour operators, and Tanzania Tour Guides Association offer astro-tourism services. Overall, majority of Tanzania’s visitors said they would return if there were new tourist offers. Similarly, majority of the inbound visitors expressed willingness to return if Tanzania embraces astro-tourism. Conversely, majority of the domestic visitors seemed that were not aware of astro-tourism as one of the tourist products. Future research may focus on profiling astronomical cultural heritage in Tanzania.